Technical aspects of physical implementation of an active noise control system: challenges and opportunities - Maja Anachkova, Simona Domazetovska, Petreski Zlatko, Viktor Gavriloski (Institute of Noise Control Engineering, 2022)
Active noise control systems have become a subject of intensive worldwide research that have aroused considerable interest as being a promising solution to the problem of low-frequency noise control. Advanced real-time signal processing technologies offer opportunities that have been adopted in many active noise control industry applications, as well as in the modern urban environment where noise reduction is gaining priority status. Depending on the application, the concept of active sound control can be implemented using different control strategies. The development and application of such systems requires in-depth knowledge and theoretical analysis in the field of digital signal processing, sensor technology, adaptive control, understanding in hardware solutions for acquisition and data processing, as well as software capabilities for modeling, visualization and control of signals. Also, the construction of such a system must give an overview of the choice and characteristics of its components in terms of the impact of the elements that make it up on its accomplishment. This paper provides an insight into the engineering aspects for implementation of an active noise control system in a duct, emphasizing the technical requirements that need to be analyzed and might further affect the systems overall performance.